THE RELATIONSHIP OF ENTREPRENEURIAL SOUL AND INTRODUCTION OF INFORMATION TECHNOLOGY TO UNDERSTANDING OF ACCOUNTING INFORMATION QUALITY - MF DJENI INDRAJATI WIDJAJA; ELIZABETH SUGIARTO DERMAWAN (Jurnal Bisnis dan Akuntansi, 2020)
This research was conducted to illustrate the readiness of S1 Accounting students in entrepreneurship and their readiness to compete through familiar information technology that can relate to their understanding of the quality of accounting information that is ultimately needed for decision making and accountability. The results of this study indicate the link between the Entrepreneurial Soul and the introduction of positive and significant information technology to the quality of accounting information. By looking at the correlation coefficient, Entrepreneurial Soul has a higher correlation coefficient on understanding Accounting Information Quality than Introduction to Information Technology on understanding Accounting Information Quality. Therefore, in order to increase understanding of the Quality of Accounting Information, it is necessary to improve the Entrepreneurial Soul and Introduction of Information Technology.